The internationalisation of production: Moving plants, products, and people - Armin Riess; Kristian Uppenberg (EIB Papers, 2004)
Introducing this volume of the EIB Papers and linking the various contributions, this paper emphasises that the internationalisation of production in Europe, which creates cross-border production networks, is an increasingly important element of globalisation, has been spreading to new EU members, and brings benefits very similar to those of globalisation in general. Popular fears that the geographical reorganisation of production comes at the expense of countries that see some of their activities moving to other countries are largely unfounded. In particular, 'races to the bottom' in wages, tax revenues, and environmental standards do not seem to take place. On the contrary, the move appears to be up rather than down. That said, like any structural change, the internationalisation of production brings distributional challenges that need to be dealt with.
Keywords: 330; Betriebliche Standortwahl; Standortwettbewerb; Standortfaktor; Direktinvestition; Multinationales Unternehmen; EU-Staaten